2013
DOI: 10.1016/j.carpath.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of left and balanced coronary arterial dominance decreases with increasing age of patients at autopsy. A postmortem coronary angiograms study

Abstract: In this large autopsy cohort, the prevalence of a left dominant or codominant coronary system decreased with increasing age. These findings could relate to a slightly higher risk of mortality in case of left versus right coronary artery occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 12 publications
1
25
1
Order By: Relevance
“…A recently published post-mortem angiography study showed that the prevalence of left and balanced dominance decreased with increasing age 3 , while we found no relation between age and dominance pattern in the population of TWENTE trial patients, who were on average at a younger age (being normally distributed) than the population of the aforementioned post-mortem study that also comprised a wider age range (with non-Gaussian distribution).…”
Section: Clinical Outcomecontrasting
confidence: 89%
See 2 more Smart Citations
“…A recently published post-mortem angiography study showed that the prevalence of left and balanced dominance decreased with increasing age 3 , while we found no relation between age and dominance pattern in the population of TWENTE trial patients, who were on average at a younger age (being normally distributed) than the population of the aforementioned post-mortem study that also comprised a wider age range (with non-Gaussian distribution).…”
Section: Clinical Outcomecontrasting
confidence: 89%
“…A few registries and studies have shown relations between left dominance and inferior clinical outcome [2][3][4] , but the patient populations of these studies differed significantly from that of the TWENTE trial 5 .…”
Section: Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, the increased mortality may possibly be because of an unbalanced vascular supply and higher procedural risk during PCI . This explanation is supported by a post‐mortem study in which it was found that the prevalence of LD coronary circulation decreased with age reflective of a higher mortality rate in LD circulation . Moreover, one of the studies included in our meta‐analysis also showed a higher proportion of LD in patients who died .…”
Section: Discussionsupporting
confidence: 74%
“…The mechanism of a potentially increased susceptibility to coronary events in patients with left dominant anatomy is to date unclear. A study screening postmortem angiograms showed that the prevalence of a left dominant system decreased with age, suggesting a higher death rate among patients with a left dominant coronary artery system 26. An explanation could be the larger myocardial area at risk in case of an acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%